Síntese e cristaloquímica de complexos de Hg(II) e Ni(II) com o ligante 1,3-BIS(4-bromofenil)triazenido - Behm, Mariana Boneberger (2006)
Deprotonated 1,3-Bis(4-bromophenyl)triazene reacts with Hg(CH3COO)2 in methanol yielding [Hg(BrC6H4NNNC6H4Br)2]∞ (1) a triazenide complex polymer of Hg(II). The crystal structure of (1) reveals one-dimensional infinite chains along the [010] direction through Hg−η2, η2−arene π−interactions. The crystal system of 1 is monoclinic and belongs to the space group P21/n with the cell parameters a = 15.1741(6) Å, b = 4.6587(2) Å, c = 18.5342(7) Å, β = 94.207(2)°. The crystal structure refinement converge to the final indices R1 = 0.0278, wR2 = 0.0798. A mixture of nickel(II) chloride in methanol/THF reacts with deprotonated 1,3-Bis(4- bromophenyl)triazene to give cis-Bis{[1,3-(4-bromophenyl)triazenido](pyridine)}nickel(II) (2), a mononuclear complex with Ni(II) showing a rhombic distorted coordination geometry. In the solid state complex 2 reveals one-dimensional infinite chains with the base vector 0 1 0 as result of intermolecular C−H···Br no classic hydrogen bonds. The crystal structure of 2 belongs to the monoclinic system and the structure was solved with the space group P21/c and the cell parameters a = 10.4677(5) Å, b = 19.6783(9) Å; c = 17.5083(9) Å, β = 91.681(3) °. The structure refinement converges to the final indices R1 = 0.0367, wR2 = 0.0924. Beside the single crystal structure analysis of 1 and 2, both compounds were also characterized by infrared an UV/VIS spectroscopy.